New perspective on the transition from flat to steeper subduction in Oaxaca, Mexico, based on seismicity, nonvolcanic tremor, and slow slip. Issue 3 (19th March 2016) - Fasola, Shannon; Brudzinski, Michael R.; Ghouse, Noorulann; Solada, Katharine; Sit, Stefany; Cabral‐Cano, Enrique; Arciniega‐Ceballos, Alejandra; Kelly, Nicholas; Jensen, Kevin
Abstract: We examine the along‐strike transition from flat to steeper subduction in Oaxaca, Mexico, to provide a better understanding of what controls the slab morphology. Prior studies have suggested the slab tends to tear along the transitions in dip as the slab rolls back. We determine the slab geometry based on local seismicity, nonvolcanic tremor (NVT), and slow slip utilizing a deployment of broadband seismometers and continuous GPS receivers distributed in and around Oaxaca. We construct depth contours of the subducting slab surface down to 100 km, which illustrate that the transition from flat to steeper subduction occurs rapidly via a sharper flexure than previously recognized. The prior catalog of NVT in Oaxaca is extended using the same method and additional stations that extend further west. The band of NVT follows the new slab contours, widening toward the west with the downdip extent gradually moving inland. The amount of NVT also correlates with the strength of an ultraslow‐velocity layer. There are no gaps in seismicity, NVT, or slow slip across the rapid transition in slab dip, further supporting the notion that the slab is not currently torn in the updip region. We propose that the sharp flexure is possible in this region due to bending moment saturation that leads to greater curvature in both the downdip and along‐strike directions. A similar set of observations in southern Peru suggests this is a viable alternative to tearing that accommodates the large strains from variable rates of slab rollback. Key Points: New slab surface contours reveal sharp curvature from flat to steeper subduction Seismicity, NVT, and SSEs indicate subducting slab is continuous across sharp transition in dip Sharp flexure is possible in this region due to bending moment saturation